(untitled) (Research, Society and Development, 2019)
This article is inserted in the scope of construction planning, and it sought to compare construction techniques aiming at their best cost benefit, seeking to achieve efficiency and economy for the project proposed and maintaining the quality of the service. It is of utmost relevance to understand more deeply the various execution procedures provided by engineering because they tend to clarify the pros and cons of the project, which is essential for the decision making process. This work aims to carry out a comparative study between two technologies of formwork performance, using metallic and wooden materials. The study was carried out through the application of these technologies in the planning of the construction project of the Teaching Pavilion of the Military School of Belém, Pará, using a reference pricing list from the Secretariat of Public Works of the State of Pará. The study analyzed the labor cost, the material and the total value of each construction technique as well as their respective execution time. It was verified that the wooden formwork presented greater viability, representing an economy of approximately 14% in relation to the metallic formwork for the project aforementioned. Therefore, for the case analyzed, the wooden formwork proved to be more viable, reducing the construction cost by approximately R 130,000.